INDUCED SPAWNING OF THE COMMON SNOOK, Centropomus undecimalis, IN CAPTIVITY USING GnRH-a IMPLANTS - Contreras García, María de Jesús; Contreras -Sánchez, Wilfrido Miguel; Hernández-Vidal, Ulises; Mcdonal-Vera, Alejandro (Ecosistemas y Recursos Agropecuarios, 2015)
Culture of C. undecimalis shows great potential as this species tolerates handling and adapts easily to captivity. However, the difficulty in achieving spawning in captivity is a major obstacle for the development of commercial scale farming. Spawning of common snook was achieved using GnRH-a implants in single 100 and 200 µg doses per fish; control group specimens received no hormone and did not spawn. Both GnRH-a trial doses resulted in spawning with up to 100% fertilization rates per experimental unit, and a range of 60 – 76% per treatment.  A 50 – 100% hatching rate was obtained and larvae were between 1.56 ± 0.08 and 1.98 ± 0.05 mm total length after yolk sac absorption.